International Geoscience and Remote Sensing Symposium (IGARSS) (2003)
The Three Gorges Dam Project (TGP) has raised international attention because of its great potential for hydroelectrical power generation and flood control, as well as for its potentially hazardous effects on the environment and ecology, and for the migration and resettlement of local inhabitants. Slope instability is one common problem in the Three Gorges area and this paper reports a regional assessment of landslide hazard based on ASTER imagery and Digital Elevation Model (DEM), in combination with limited field investigation. A simple model based on the geometric mean and Boolean decision rules has been applied to a multi-criterion dataset to generate a map of landslide hazard.